Antivasoconstrictor and Antiaggregatory Activities of Picotamide Unrelated to Thromboxane A2 Antagonism - Vezza, Roberta; Spina, Domenico; Tallarida, Ronald J; Nathan, Malevika; Page, Clive P; Gresele, Paolo (Thrombosis and Haemostasis, 1997)
Picotamide is a dual thromboxane (Tx) A2 receptor antagonist/Tx synthase inhibitor although some observations suggest an anti-vasoconstrictor effect independent of TxA2 inhibition/antagonism. The aim of our study was to assess whether picotamide antagonises vascular contractions induced by different vasoactive substances in vitro. Picotamide inhibited competitively the contraction of rabbit aortic rings induced by the TxA2 mimetic U46619 (pA2 = 3.59) but also the contractions induced by phenylephrine (pA2 = 3.93) and serotonin (5-HT) (pA2 = 5.81) although in a not competitive way. Picotamide did not inhibit potassium-induced contractions, thus excluding aspecific effects on vascular smooth muscle. Picotamide inhibited 5-HT-induced platelet aggregation in vitro with an IC50 (212 μM) similar to that found when other aggregating stimuli are used, but it did not affect shape change (IC50> 1 mM) suggesting that the effects of picotamide can not be ascribed to 5-HT2-receptor antagonism; in the same experimental conditions neither a Tx-receptor antagonist (BM13.177) nor a dual Tx-receptor antagonist/synthase inhibitor (ridogrel) affected 5-HT-induced platelet responses.Our studies demonstrate that picotamide exerts antivasoconstrictor and platelet inhibitory effects unrelated to TxA2 antagonism. This activity may contribute to the anti-thrombotic/anti-ischaemic effects of the drug in vivo.